Neologisms, Loanwords, and Arabized Terms in Contemporary Arabic Football Terminology in Al Jazeera Media: A Study of the Coverage of the 2022 FIFA World Cup in Qatar - Ela Saela; Nafisa Hashifatuzahra; Novy Maryani (Gunung Djati Conference Series, 2026)
This study examines neologisms in football terminology in the coverage of the 2022 FIFA World Cup in Qatar by the Arab media outlet Al Jazeera, focusing on three categories: neologisms, dakhil (loanwords), and mu‘arrab (Arabized terms). It aims to understand how modern Arabic adapts global terms without losing its identity, as well as how new terms shape contemporary football vocabulary. The study employs a descriptive qualitative method, using digital news texts as data and analyzing them inductively through reduction, classification, and interpretation. The findings show that neologisms emerge through the extension of existing Arabic vocabulary or the creation of new phrases to explain rules, technologies, and game strategies. Dakhil retains foreign terms according to international standards, while mu‘arrab adapts them to make them easier to read and pronounce in Arabic. These three categories complement each other, making media Arabic flexible, adaptive, and communicative. The findings contribute to the development of modern Arabic vocabulary, language learning, and the understanding of international sports terminology.